Comparing the spatial information in offensive strategy and scoring style between winning and losing teams of basketball games - Lan, Y. C.; Liu, Y. T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: In basketball games, coaches deploy offensive tactics on different locations on the court (Atkins, 2004). Scoring in the lane is very important but shooting from the perimeter also contributes to a successful game (Tseng, 2011). Could the outcomes of the games attribute to the patterns of shooting/scoring locations on the court? The purpose of the study was to use the principal component analysis (PCA) to identify and compare the offensive tactics in basketball games based on the shooting and scoring zones between winning and losing teams. Methods: All games (n= 32) from 2012-2014 Taiwanese University Basketball Association (UBA) men`s division I were recorded and a total of 5296 shootings were analyzed. The court was divided into five zones (Z1: the lane, Z2: 2-point high zone, Z3:2-point low zone, Z4: 3-point high zone, Z5: 3-point low zone). Two independent observers recorded all the shots and the Cohen`s Kappa for intra and inter-rater reliability was 0.9 and 0.78, respectively. PCA was performed on the shooting zones and scoring zones for the winning teams and losing teams. Results: For the shooting zones, both winners (85.38%) and losers (86.89%) had 3 PCs that had eigen values larger than 1. For the winners, PC1 (36.46%) consisted of Z1 and Z5, PC2 (27%) consisted of Z3and Z4, PC3 (21.93%) consisted of Z2. For the losers, PC1 (38.97%) consisted of Z1, Z5, Z4, PC2 (26.51%) consisted of Z3, PC3 (21.41%) consisted of Z2. For the scoring zones, winners had 3 PCs (86.72%) and losers had 2 PCs (69.78%) that had eigen values larger than 1. For the winners, PC1 (31.69%) consisted of Z1and Z4, PC2 (31.59%) consisted of Z 5and Z2, and PC3 (23.45%) consisted of Z3. For loser, PC1 (43.04%) consisted of Z1, Z4, and PC2 (26.74%) consisted of Z3and Z5. Discussion: Based on the shooting zones results, in addition to the lane and the 3-point offensive strategy that both the winning teams and losing teams had, the winners showed another offensive pattern, which included the low post zone and the high 3-point zone. The results from the scoring zones also showed similar patterns for the winners and losers where both the lane and the 3-point high zone had the highest contributions. However, the opposite signs of the coefficient of the 2 zones for the losing teams indicated that the scoring contributions of the 2 zones were negatively correlated whereas the scoring contributions for the 2 zones from the winning teams were positively correlated. Generally speaking, both winning teams and losing teams had similar offensive strategies in terms of the shooting and scoring deployment. It is the results of the offensive strategies that determined the outcomes of the games.